2018
DOI: 10.1002/cssc.201701902
|View full text |Cite
|
Sign up to set email alerts
|

Cascade Production of Lactic Acid from Universal Types of Sugars Catalyzed by Lanthanum Triflate

Abstract: Lignocellulosic biomass conversion into value-added platform chemicals in the non-toxic, water-tolerant Lewis acid, and water solutions bears the hallmark of green chemistry. Lactic acid derived from biomass is an important chemical building block for biodegradable polymers such as polylactide. Herein, a universal method of converting lignocellulosic sugars into lactic acid using catalytic amount of water-stable Lewis acid La(OTf) is demonstrated. The lignocellulosic sugars studied in this work include 1) pyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 44 publications
0
22
0
2
Order By: Relevance
“…139 Lactic acid was also prepared by a simple universal method using a La(OTf ) 3 water resistant Lewis acid. 140 They demonstrated that under moderate conditions (250°C, 1 h) levoglucosan was transformed to lactic acid with the total yield was 75%. This yield was comparable to that obtained with other sugars such as glucose and xylose (74 and 64% respectively).…”
Section: Green Chemistry Critical Reviewmentioning
confidence: 99%
“…139 Lactic acid was also prepared by a simple universal method using a La(OTf ) 3 water resistant Lewis acid. 140 They demonstrated that under moderate conditions (250°C, 1 h) levoglucosan was transformed to lactic acid with the total yield was 75%. This yield was comparable to that obtained with other sugars such as glucose and xylose (74 and 64% respectively).…”
Section: Green Chemistry Critical Reviewmentioning
confidence: 99%
“…To increase productivities, working with more concentrated feedstock, the catalytic strategy could be an alternative. Liu et al have recently proved that pyrolytic sugars (levoglucosan, glucose and xylose) can be converted in acceptable yields to LA (75, 74 and 61% based on C content) using lanthanum triflate, a Lewis acid catalyst [85]. This approach can be successfully extended to cellulose (73% C yield).…”
Section: Direct Reactions Of Xylose To Alcohols Acids and Polymersmentioning
confidence: 99%
“…Nevertheless, very few studies researched LA production directly from cellulosic biomass, due to the complexity of biomass structures (i.e., cellulose, hemicellulose, and lignin), along with the catalyst deactivation induced by lignin [89]. Interestingly, Liu et al presented a valuable work regarding LA production directly from lignocellulosic sugars including levoglucosan, glucose, and xylose with good yields [70]. Using a Lewis acid catalyst, La(OTf ) 3 which is stable in both aqueous and organic solvent, 61% LA yield for C 5 sugars and >70% LA yield from C 6 sugars could be obtained.…”
Section: 22mentioning
confidence: 99%